Performances de croissance de l'huître creuse, Crassostrea gigas (Thunberg) dans le bassin d'élevage de Marennes-Oléron entre 1979 & 1982 - Berthome, Jean-paul; Prou, Jean; Bodoy, Alain (Société Française de Malacololgie, 1986)
Growth of the japanese oyster, Crassostrea gigas was monitored during 4 years, by following the recruitment of the year 1978, held in rearing conditions. After three and half years, the average length was la cm and the average total weight was 80 g. Clear seasonal changes were observed on the growth in length and weight. An important loss in dry weight occured in July, during the release of gametes. Such losses constituted 29 %, 43 % and 60 % of the dry weight, respectively for individuals which were 2 years, 3 years and 4 years old. The higher instantaneous growth rates (G) were observed during spring and at the beginning of summer. Growth model of Von Bertalanffy, gave the best estimate for the length growth of the species. During the 1979-1982 period, growth was clearly slower then that was observed in the early seventies, when the species was introduced in the area. It was also slower, if compared with other rearing areas or with experiments reproducing the field environment. Such a decrease in the growth performance was related with the high level of the reared stock in the Marennes-Oleron area. La croissance de l'huître Crassotrea gigas a été suivie sur une période de 4 ans, à partir d'individus captés en 1978, et placés en conditions d'élevage. L'évolution de la longueur et du poids total montre que la population atteint une taille de la cm et un poids de 80 g en trois ans et demi. Les croissances linéaire et pondérale présentent des fluctuations saisonnières marquées. Il se produit notamment une perte de poids sec très importante, lors de l'émission des gamètes en juillet, ce qui révèle' l'importance quantitative de la reproduction de l'huître dans le bassin de Marennes-Oléron. Celle-ci représente 29 %, 43 % et 60 % du poids sec pour des huîtres âgées de 2, 3 et 4 ans. Les plus forts taux instantanés de croissance (G) se rencontrent au printemps et au début de l'été. Le modèle de Von Bertalanffy s'est avéré le plus apte à décrire la croissance linéaire de l'espèce. Les performances de croissance ...